2022
DOI: 10.4018/978-1-7998-9235-9.ch011
|View full text |Cite
|
Sign up to set email alerts
|

Technology Integration in the Post-Pandemic Secondary Classroom

Abstract: This chapter examines the existing literature surrounding educational technology in secondary classrooms both before and during the ERT as a result of the novel coronavirus pandemic in 2019–2021. The researchers synthesize digital learning, 1:1 and BYOD initiatives, PLCs, and TPACK in order to both describe the current state of secondary classroom technology integration as well as to make informed recommendations about necessary future research. The researchers suggest that TPACK provides a useful framework fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…They highlighted the need to investigate the actual use of the technologies integrated into educational systems as students might use them for leisure or personal use rather than academic activities, with negative effects on their academic performance. Hanshaw et al (2022) concurred and added that students tend to focus on chatting and visiting social networks. Tanik Önal (2021) conducted a survey to identify the activities that students engage in using technological devices.…”
Section: Literature Reviewmentioning
confidence: 94%
See 2 more Smart Citations
“…They highlighted the need to investigate the actual use of the technologies integrated into educational systems as students might use them for leisure or personal use rather than academic activities, with negative effects on their academic performance. Hanshaw et al (2022) concurred and added that students tend to focus on chatting and visiting social networks. Tanik Önal (2021) conducted a survey to identify the activities that students engage in using technological devices.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Studies have found that spending an excessive amount of time on the Internet can cause psychological distress such as anxiety, insomnia, social seclusion and depression which in turn negatively affects academic achievement (Banoǧlu & Gümüş, 2022;Kroesch et al, 2022). Hanshaw et al (2022) found that the amount of time students devote to academic work while using a computer and the Internet varies. They concluded that the total amount of time an individual devotes to the use of technology is a function of their motives for such use.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation